2020
DOI: 10.1039/d0ta07066a
|View full text |Cite|
|
Sign up to set email alerts
|

Two-dimensional semiconducting covalent organic nanosheets for highly sensitive and stable NO2 sensing under humid conditions

Abstract: Semiconductor metal oxide gas sensors do not provide selective and sensitive gas adsorption under humid conditions owing to the deactivation of active sites by environmental humidity, leading to inaccurate signal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…The average basal spacing of the bright regions (Regions 1–3) was estimated as 3.4 nm, which is almost identical to the known value for GNs (Figure S7, see Supporting Information). In contrast, that of the relatively dark region (Region 4) was estimated as 3.6 nm, indicating CON phases which were proven in the previous literature with fast Fourier transform (FFT) [48] . Therefore, it could be suggested that CONs formed framework structures on GNs surfaces rather than existed in amorphous polymers even though CONs did not show diffraction peaks in PXRD (Figure 2b).…”
Section: Resultsmentioning
confidence: 51%
“…The average basal spacing of the bright regions (Regions 1–3) was estimated as 3.4 nm, which is almost identical to the known value for GNs (Figure S7, see Supporting Information). In contrast, that of the relatively dark region (Region 4) was estimated as 3.6 nm, indicating CON phases which were proven in the previous literature with fast Fourier transform (FFT) [48] . Therefore, it could be suggested that CONs formed framework structures on GNs surfaces rather than existed in amorphous polymers even though CONs did not show diffraction peaks in PXRD (Figure 2b).…”
Section: Resultsmentioning
confidence: 51%
“…Through physical or chemical interactions, absorbed analytes change the internal environment and thereby affect the electroactivity. This mechanism of sensing can be integrated into various device architectures, including resistive sensors [78,79], FET-type sensors [80][81][82], and synaptic sensors [83]. For instance, utilizing the binding potential towards Ni-phthalocyanine incorporated in a COF for various analytes, chemiresistive devices based on this COF show a highly sensitive response to a series of gases like NH 3 , H 2 S, NO, and NO 2 (Figure 5A) [12].…”
Section: Sensors Electrochromic Devices and Memory Devicesmentioning
confidence: 99%
“…With semiconductivity and recognition ability, COFs can act as the active layer in OFET-based sensors. The semiconducting CON-10 was utilized to fabricate a NO 2 sensor with a super-hydrophobic surface [80]. As a result, the device showed a humidity-independent NO 2 response with high sensitivity in the humidity range of 0-87%.…”
Section: Sensors Electrochromic Devices and Memory Devicesmentioning
confidence: 99%
“…The sensing materials prepared by this method can not only highlight the sensing advantages of the quantum crystal itself but also provide channels for efficient carrier transmission, resulting in a signicant improvement in the sensing performance. 21,22 Covalent organic frameworks (COFs) are a class of twodimensional covalently constructed organic crystal materials with pre-designed properties owing to the low-dimensional pelectronic skeleton and highly ordered topology. These components are arranged into periodic planar networks, and nally superposed in the vertical direction to form a layered structure with consistent atomic accuracy.…”
Section: Introductionmentioning
confidence: 99%